NGO–business collaboration following the Indian CSR Bill 2013: trust-building collaborative social sector partnerships. Issue 6 (18th August 2018) - Jayaraman, Anuja; D'souza, Vanessa; Ghoshal, Trisha
ABSTRACT: The CSR Bill of 2013 introduced systematic corporate participation into social development in India. In the light of this law, this article argues that NGOs will play a decisive role in determining the benefits of corporate involvement and recommends that NGO–business partnerships are needed for meaningful social change. The article identifies a trust deficit between NGOs and businesses in India as a key obstacle to the success of NGO–business collaborations in the social sector. It suggests practices that could be adopted by NGOs to build trust in their partnerships with business partners, using a case study of one NGO, SNEHA (Society for Nutrition, Education and Health Action).